PERANCANGAN SISTEM INFORMASI PEMESANAN DAN WORKSHOP ONLINE BERBASIS WEBSITE PADA TOKO KIBO'S KITCHEN - Indy Rahmah Nisrina (2023)
Kibo's Kitchen is a cake and ready-to-eat food shop that provides services in the food sector. For now the process of ordering cakes at Kibo's Kitchen is still done manually, customers must visit several Kibo's Kitchen stands directly to buy cakes or for ordering customers can contact Instagram Kibo's Kitchen via dm. This causes purchasing activities to be less effective and efficient. Apart from ordering Kibo's Kitchen, we also occasionally open workshops to learn how to make cakes which are taught directly by the owner. With a website-based ordering information system and online workshops, it makes it easier for customers to complete transactions without having to come to a stand or venue. The research method taken is a qualitative method, namely interviewing the owner of the Kibo's Kitchen cake directly. The procedure improvement technique used in this research is the waterfall method. The waterfall method is a sequential method. In this ordering system and online workshop, the author utilizes UML and MYSQL diagrams in the data, and this system is made by taking the MySQL, HTML and PHP programming languages as databases. The result of this research is a cake ordering information system that has been computerized and the system can speed up sales data. After evaluating the current business transaction system, researchers hope to make it easier for cake business organizations to manage customer and consumer data in conducting business transactions.